2008
DOI: 10.1039/b718480h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of proton transfer in Nafion®: elementary reactions at the sulfonic acid groups

Abstract: Proton transfer reactions at the sulfonic acid groups in Nafion were theoretically studied, using complexes formed from triflic acid (CF3SO3H), H3O+ and H2O, as model systems. The investigations began with searching for potential precursors and transition states at low hydration levels, using the test-particle model (T-model), density functional theory (DFT) and ab initio calculations. They were employed as starting configurations in Born-Oppenheimer molecular dynamics (BOMD) simulations at 298 K, from which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 48 publications
1
68
0
Order By: Relevance
“…Since the vibrational energies for the interconversion between the oscillatory shuttling and structural diffusion motions (Dm OH;MD BA ) in the intermediate states (n ¼ 1 and 3) are ranging from 4.8 to 10.5 kJ/mol, it is reasonable to anticipate that the thermal energy fluctuation and dynamics in the short H-bond chains are sufficient to activate the structural diffusion process (at 298 K the experimental activation enthalpy is 8.4 kJ/mol), without the requirement of H-bond weakening or cleavage anywhere. As our previous and present results concluded that proton transfer reactions in H-bonds are not concerted, [7][8][9]19] covalent bond breaking and forming need not occur in a single step, and the ratedetermining steps are associated with the lifetimes of the quasi-dynamic equilibriums between the shared-proton and close-contact structures (not the proton displacement within a single H-bond), elementary steps which involve fluctuation of the number of the CH 3 OH molecules in the H-bond chains (n ¼ 3 and n ! 4) could be formulated, using the H-bond chains with n ¼ 3-5 as examples.…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…Since the vibrational energies for the interconversion between the oscillatory shuttling and structural diffusion motions (Dm OH;MD BA ) in the intermediate states (n ¼ 1 and 3) are ranging from 4.8 to 10.5 kJ/mol, it is reasonable to anticipate that the thermal energy fluctuation and dynamics in the short H-bond chains are sufficient to activate the structural diffusion process (at 298 K the experimental activation enthalpy is 8.4 kJ/mol), without the requirement of H-bond weakening or cleavage anywhere. As our previous and present results concluded that proton transfer reactions in H-bonds are not concerted, [7][8][9]19] covalent bond breaking and forming need not occur in a single step, and the ratedetermining steps are associated with the lifetimes of the quasi-dynamic equilibriums between the shared-proton and close-contact structures (not the proton displacement within a single H-bond), elementary steps which involve fluctuation of the number of the CH 3 OH molecules in the H-bond chains (n ¼ 3 and n ! 4) could be formulated, using the H-bond chains with n ¼ 3-5 as examples.…”
mentioning
confidence: 63%
“…It was iterated that static proton transfer potentials cannot provide complete description of proton transfer reactions and the thermal energy fluctuation and dynamics must be incorporated in the model calculations. [7][8][9] To continue the series of theoretical studies on small H-bond systems, [7][8][9]19] as well as to obtain additional explanations for the proposed mechanisms, [13,15] structures, energetic and dynamics of proton transfer processes in protonated H-bond chains were investigated in the present work, using the CH 3 OH þ 2 (CH 3 OH) n complexes, n ¼ 1-4, as model systems, and B3LYP/TZVP calculations and BOMD simulations as model calculations. Since the effects of electron correlations could be important in the present model systems and it has been our intention to apply the DFT method in larger H-bond complexes, some static and dynamic results, obtained based on B3LYP/TZVP calculations, were examined using ab initio calculations at the RIMP2/TZVP level of accuracy.…”
Section: Oh;md Bamentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally to the limited number of published experimental data [12,22] the diffusion coefficient of any ion appears to be strongly dependent on its concentration and the presence of other ions. This especially applies to protons, whose exact transport mechanism in Nafion under different conditions may change and is still in debate [25].…”
Section: Sources Of Error For the Resistance Calculationmentioning
confidence: 99%